Long-term Follow-up Results of Regeneration Process of Fungiform Taste Buds After Severing the Chorda Tympani Nerve During Middle Ear Surgery. (May 2016) - Saito, Takehisa; Ito, Tetsufumi; Ito, Yumi; Manabe, Yasuhiro
Objective: To elucidate the regeneration process of fungiform taste buds after severing the chorda tympani nerve (CTN) by confocal laser scanning microscopy in vivo. Methods: In 7 consecutive patients whose CTN was severed during tympanoplasty, an average of 10 fungiform papillae in the midlateral region of the tongue were periodically observed, and the number of taste buds was counted until 12 to 24 months after surgery. Gustatory function was assessed by EGM. Results: EGM thresholds showed no response within 1 month after surgery in any patient. All taste buds had disappeared until 13 to 71 days after surgery. Regenerated taste buds were first detected 5 to 8 months after surgery in 5 of the 7 patients. EGM thresholds recovered to their preoperative values in 2 patients. In these 2 patients, the number of regenerated taste buds gradually increased in combination with a recovered taste function. However, a time lag existed between taste bud regeneration and taste function recovery. EGM thresholds did not recover in the other 3 patients with regenerated taste buds, suggesting that these taste buds were immature without gustatory function. Conclusion: The long-term regeneration process of fungiform taste buds could be clarified using confocal laser scanning microscopy.